Leaf Stoichiometry of Potentilla fruticosa Across Elevations in China’s Qilian Mountains - Qin, Yanyan; Liu, Wei; Zhang, Xiaofang; Adamowski, Jan F.; Biswas, Asim (Frontiers in Plant Science, 2022)
As an individual plant species can develop its own leaf stoichiometry to adapt to environmental changes, this stoichiometry can provide critical information about a plant species’ growth and its potential management in the ecosystem housing it. However, leaf stoichiometry is largely undocumented at regions with large environmental changes arising from differences in elevation. The leaf stoichiometry of Potentilla fruticosa L., a major alpine shrub playing an important role in supporting ecosystem functions and services in China’s Qilian Mountains (Northeast Qinghai-Tibetan Plateau) was investigated at different elevations (2,400 m, 2,600 m, 2,800 m, 3,000 m, 3,200 m, 3,500 m and 3,800 m). At each elevation, leaf elemental (C, N, and P) concentrations were measured in P. fruticosa leaves sampled from three plots (10 m × 10 m) and edaphic properties were assessed in nine quadrats (1 m × 1 m, three quadrats per plot), Temperature and precipitation were calculated using an empirical formula. Maximum and minimum leaf carbon (C) concentrations ([C]leaf) of 524 ± 5.88 g kg-1 and 403 ± 3.01 g kg-1 were measured at 2,600 m and 3,500 m, respectively. Leaf nitrogen (N) concentration ([N]leaf) showed a generally increasing trend with elevation and peaked at 3,500 m (27.33 ± 0.26 g kg-1). Leaf phosphorus (P) concentration ([P]leaf) varied slightly from 2,400 m to 3,200 m, then dropped to a minimum (0.60 ± 0.10 g kg-1) at 3800 m. The [C]leaf:[N]leaf, [C]leaf:[P]leaf and [N]leaf:[P]leaf varied little from 2,400 m to 3,000 m but fluctuated somewhat at higher elevations. The main factors affecting P. fruticosa leaf stoichiometry were soil organic C, pH, and soil total P, and the main limiting element for the growth of P. fruticosa in the study area was P. In conclusion, changes in elevation affected leaf stoichiometry of P. fruticosa mainly due to altered soil properties, and addressing phosphorus limitation, especially at higher elevations mainly due to losses caused by high precipitation and sparse vegetation, is a key measure to promote P. fruticosa growth in this region.